Communication Relations Of The Secretariat Of The Regional House Of Representatives Of North Sumatra Province In Improving Legislative And Executive Harmonization (Perspective Of Islamic Communication) - Luthfi Solihin; Syukur Kholil; Elfi Yanti Ritonga (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research looks at the communication relations of the Secretariat of the Regional People’s Representative Council of North Sumatra Province in improving legislative and executive harmony (Islamic communication perspective). The research results show that the communication relationship between the Secretariat of the Regional People’s Representative Council (DPRD) of North Sumatra Province in improving legislative and executive harmonization can be concluded as follows: First, the communication relationship between the Secretariat (DPRD) of North Sumatra Province in increasing legislative and executive harmonization, namely: Secretariat ( DPRD ) North Sumatra Province has prepared agendas, logistics and meeting schedules between legislative and executive members, controlled information and documentation, has prepared meeting minutes and reports, has organized joint activities between the legislative and executive and has made public information. Second, the strategy used for North Sumatra Province Secretariat (DPRD) Communication Relations in Improving Legislative and Executive Harmonization, namely: The North Sumatra Province Secretariat (DPRD) has implemented a strategy to increase routine coordination and collaboration, implemented a strategy to strengthen internal communication, built a strategy of trust and relationships personal, implementing alignment of goals and shared vision to be able to work together better. Third, factors that influence obstacles to North Sumatra Province Secretariat (DPRD) Communication Relations in Improving Legislative and Executive Harmonization, namely differences in goals and interests, lack of transparency in communication, limited human resources (HR), unclear duties and responsibilities, political and social instability and differences in understanding of policy and the legislative process.